Building a Model of Education Based Character - Ifada Retno Ekaningrum (Proceeding Of The International Seminar and Conference on Global Issues, 2016)
This article discusses the character-based education model, which is seen from substance classified as value-based education. Thought values-based education based on the experience of history, where there has been a reduction in the value of education, so that its output becomes dry when the value falls in the community. The empirical evidence is difficult to solve corruption, violation of rules became the scene of daily violence in the resolution of social problems often occur, the loss of national character adi Luhung in the younger generation. Subo sito, tata krama , andap asor be a costly item in the interaction between the old and the young. Erosion of national values ​​and local wisdom, has actually started in school. The curriculum structure built on the basis filasafat positivistic, emphasizes cognitive, so slowly but surely, moral education is reduced. Terkesampingkan transcendental truth, truth is replaced with logical, empirical, nomotetik and mechanistic. From there it takes the review towards character-based education. Character Counts in America identifies dimensional characters who made the pillars formulating the direction of education, among others: (1) to be believed (trustzoorthiness); (2) respect and attention (respect); (3) responsibility (responsibility); (4) honest (fairness); (5) care (caring); (6) nationality (citizenship); (7) sincerity (honesty); (8) daring (courage); (9) diligent (diligence); and (10) integrity. Viewed from the standpoint of the process and learning time, character-based education is done in a long time range, which involves internal schools, families and communities. In line with his character, character-based education should be built through entering religious values ​​as a reflection of the character into consideration the state philosophy, empirical experience both, theoretical guides and local knowledge, to go through the process of transformation, habituation, acculturation and empowerment. With this pattern, cultivation of character is expected to do. Keywords: character education, local wisdom, values ​​nationality